Bentuk dan Dampak Kekerasan Dalam Berpacaran: Perspektif Perbedaan Jenis Kelamin - Rini Rini (Universitas Persada Indonesia YAI, 2022)
The number of violence in relationship has been increasing, this increase is not onlyhappening to women, but also to men so it is necessary needed to explore how forms ofviolence in relationship are experienced by men and women, as well as how the violenceaffects both men and women. Respondents of this study were 402 people who hadexperienced violence in relationship, either in the type of physical violence, psychologicalviolence, economic violence, activity restriction violence, or sexual violence. By usingAccidental Sampling technique a Google Forms was distributed via WhatsApp, Telegram,and email to collect data. Data analysis was carried out with a descriptive approach. Theresults of the analysis shows that women are most vulnerable to experience various typesof violence in relationship. However, men are more likely to experience the effects of theviolence itself than women.